Rheological Properties of High-Methoxyl Pectin and Locust Bean Gum Solutions in Steady Shear - Silva, J. A.Lopes da (2011)
The Cross and Carreau flow models described well the shear rate-apparent viscosity data. The coil overlap parameter, c[η], correlated well with the zero-shear rate specific viscosities of these mixtures. Experimental values of intrinsic viscosities of the mixtures were in good agreement with the prediction based on an additive model of the individual contributions of the gums. From the results obtained for the mixtures of both polysaccharide solutions at similar viscosity, pH and ionic strength, no significant interactions were detected. Hypotheses for this lack of polymer interaction were developed. Results with such model systems are useful in understanding the relation of composition to the properties of complex food systems.